Residual 201Tl activity in irreversible defects as a marker of myocardial viability - Zimmermann, Rainer Johannes; Mall, Gerhard; Rauch, Bernhard; Zimmer, Gisela; Gabel, Michael; Zehelein, Jörg; Bubeck, Bernd; Tillmanns, Harald; Hagl, Siegfried; Kübler, Wolfgang (Circulation, 1995)
Background The objective of the present study was to characterize the relation between the residual 201Tl activity in irreversible perfusion defects and the extent of irreversible myocardial damage indicated by the volume fraction of myocardial interstitial fibrosis in patients with chronic coronary artery disease. - Methods and Results Stress planar 201Tl scintigraphy with tracer reinjection at rest was performed in 37 patients with ≥75% stenosis of the left anterior descending coronary artery, and anteroseptal 201TI activity was quantified by computer-assisted placement of regions of interest from the serial myocardial images. During coronary artery bypass grafting (performed within 6±3 weeks after scintigraphy), two transmural biopsy specimens were taken from the anterior wall of the left ventricle and the amount of interstitial fibrosis was assessed by use of light microscopic morphometry. A wide spectrum of interstitial fibrosis was obtained, ranging from 15 vol% to 60 vol%. Interstitial fibrosis was similar in patients with reversible (n=11) or irreversible (n=15) tracer defects in conventional stress-redistribution images. However, interstitial fibrosis was significantly lower in patients who had enhanced regional 201Tl activity after tracer reinjection compared with those who did not have enhancement of tracer activity after reinjection (28±8 vol%, n=7, versus 41±12 vol%, n=8; P=.031). The correlation between relative poststenotic 201Tl activity and interstitial fibrosis after tracer reinjection was significantly improved compared with conventional redistribution images (r=−.622 versus r=−.851, n=15; P<.01). - Conclusions The present data demonstrate that the level of regional 201Tl activity in redistribution and, in particular, reinjection images is significantly related to the mass of preserved viable myocytes in poststenotic left ventricular myocardium. Therefore, the residual 201Tl activity provides information about viability within irreversible perfusion defects and may itself serve as marker of myocardial viability.